Associations between Vascular Endothelial Growth Factor Gene Polymorphisms and Different Types of Diabetic Retinopathy Susceptibility: A Systematic Review and Meta-Analysis. (5th January 2021) - Hu, Liming; Gong, Chunmei; Chen, Xiaoping; Zhou, Honghao; Yan, Junxia; Hong, Wenxu
Abstract : Background . Vascular endothelial growth factor ( VEGF ) gene polymorphisms have been shown to be associated with the risk of diabetic retinopathy (DR), but the results were inconsistent. The aim of this study was to systematically assess the associations between VEGF gene polymorphisms and different types of DR (nonproliferative DR and proliferative DR). Methods . Electronic databases PubMed, Embase, Web of Science, CNKI, and WANFANG DATA were searched for articles on the associations between VEGF gene polymorphisms and different types of DR up to November 6, 2019. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated, and subgroup analyses were conducted by ethnicity. Sensitivity analysis was conducted to assess the stability of the results. Publication bias was assessed by using the Egger regression asymmetry test and visualization of funnel plots. A systematic review was conducted for polymorphisms with a high degree of heterogeneity (I 2 > 75 % ) or studied in only one study. Results . A total of 13 and 18 studies analyzed the associations between VEGF SNPs and nonproliferative DR (NPDR) as well as proliferative DR (PDR), respectively. There were significant associations between rs2010963 and NPDR in Asian (dominant model: OR = 1.29, 95 % CI = 1.04 − 1.60 ); and rs2010963 is associated with PDR in total population (dominant model: OR = 1.20, 95 % CI = 1.03 − 1.41 ), either Asian (recessive model: OR = 1.57, 95 % CI = 1.04 − 2.35 ) or Caucasian (recessive model: OR = 1.83, 95 % CI = 1.28 − 2.63 ). Rs833061 is associated with PDR in Asian (recessive model: OR = 1.58, 95 % CI = 1.11 − 2.26 ). Rs699947 is associated with NPDR in the total population (dominant model: OR = 2.04, 95 % CI = 1.30 − 3.21 ) and associated with PDR in Asian (dominant model: OR = 1.72, 95 % CI = 1.05 − 2.84 ). Conclusions . Rs2010963, rs833061, and rs699947 are associated with NPDR or PDR, which may be involved in the occurrence and development of DR.